Reentry of Released Female Prisoners into the Community - Rotem, Efodi; Irit, Adamchuk (International Journal of Criminology and Sociology, 2017)
The literature shows a strong connection between lack of employment and involvement in crime, while finding employment represents a turning point in the life of the offender. This study examined the reentry to society of 126 female Israeli prisoners who participated in the Rehabilitation-Vocational Program, most of them were on parole, and others after release. It focused on the women's search for work, their “employment preparedness”, and their stability in the workplace. Despite the multi- problem nature of the released female population, the results indicate a relatively high success rate of stability in the workplace. The study indicates that employment was found after approximately two months. This interval from time of release to time of employment is consistent with the assumption that the former prisoners need a period of treatment and adjustment before entry in the workforce. The Rehabilitation-Vocational Program utilizes volunteers from the community and develops programs based on mentors who are positive role models. The findings indicate that such a model assists the former female prisoners in successfully reintagrating with the community.